2. Memorial Symposium Honoring the Work and Scholarship of Ralph E. Hoffman. (20th March 2017) - Ford, Judith
Abstract: Overall Abstract: This symposium will honor different aspects of Ralph Hoffman's work over his foreshortened career. John Krystal, chair of psychiatry at Yale University and Ralph's long-time colleague, will deliver a eulogy recalling Ralph's scholarly and provocative research. Phil Corlett, one of Ralph's newer colleagues, will discuss the work he and Ralph were doing in the years and days before Ralph's death. He will highlight this work in the broader context of the neurobiology of auditory verbal hallucinations (AVH). Iris Sommer will discuss Ralph's ground-breaking research on functional magnetic resonance imaging-guided transcranial magnetic stimulation treatment of AVH, and she will place it in the context of her own work and that of others. Jonathan Cohen will discuss computational psychiatry, as influenced by the writings of Ralph. Sarah Keedy will discuss phenomenology of AVH and its relevance to neurobiological studies of AVH; Ralph believed all work on AVH needed to be based in phenomenology.